2020
DOI: 10.3390/ma13102359
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Friction of Tool Steels and Their Comparison of Wear in Contact with ZrO2 and X46Cr13

Abstract: Tool steels are used in stamping, shearing processes, and as cutting tools due to their good mechanical properties. During their working cycle, steels are subject to aggressive conditions such as heat stress, fatigue, and wear. In this paper, three tool steels, namely X153CrMoV12, X37CrMoV5-1, and X45NiCrMo4 were selected against two types of bearing balls, ZrO2 and X46Cr1. All measurements were performed on a UMT TriboLab universal tribometric instrument under dry conditions. The main objective of the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The initial trend of irregular growth may be related to the friction adaptation period. 48 It was also observed that the COF value of SLA was slightly higher than other two groups during the stable period. And as shown as Figure 6C , the average COF of SLA (0.7 ± 0.04) was slightly higher than SLA-ZrP0.5 (0.6 ± 0.02) and SLA-ZrP0.7 (0.6 ± 0.03).…”
Section: Resultsmentioning
confidence: 83%
“…The initial trend of irregular growth may be related to the friction adaptation period. 48 It was also observed that the COF value of SLA was slightly higher than other two groups during the stable period. And as shown as Figure 6C , the average COF of SLA (0.7 ± 0.04) was slightly higher than SLA-ZrP0.5 (0.6 ± 0.02) and SLA-ZrP0.7 (0.6 ± 0.03).…”
Section: Resultsmentioning
confidence: 83%
“…During the reciprocating motion, the WC ball produces alternating shear stress and compressive stress on the coating surface, which repeatedly acts on hard phases and binder phases (Figure 10a). However, different contact states will lead to different wear results [30]. The shear stress on the coating surface and the contact state of tribo-pairs will change due to the size of the particles participating in the friction, thus resulting in different wear mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Tests using ball contact are also performed, for example, in chambers with regulated conditions, e.g., temperature [ 32 ]. Counter-samples of various shapes are also used, e.g., a cylinder cooperating with a sphere with its side [ 33 ] or front surface [ 34 ]. Using it to study composite materials, e.g., friction materials, requires proper planning of the experiment.…”
Section: Methodsmentioning
confidence: 99%